Proceedings of the 2017 International Conference on Manufacturing Engineering and Intelligent Materials (ICMEIM 2017) 2017
DOI: 10.2991/icmeim-17.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Voltage on Electrolysis and Plasma Polishing

Abstract: Abstract. Influence of voltage on material removal rate, surface roughness and power consumption were experimentally studied in this paper. Different polishing states were analyzed from standpoint of electricity transition on the basis of the polishing mechanism. The reason that material removal rate, surface roughness and electricity cost influenced by voltage was given. The experiments show that, material removal rate gradually decrease and velocity of surface roughness reduction gradually slow with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…Результаты профилометрических исследований показали снижение шероховатости поверхности боронитроцементованной стали после АЭПП: после 2 мин полирования значение Ra снижается до исходной величины для необработанного образца при незначительной убыли его массы (таблица), что подтверждает избирательность удаления материала по выпуклой части профиля поверхности, а не всего профиля [16]. Стоит отметить, что полирование в сульфатном электролите способствует дополнительному окислению поверхности [20,21] The paper discusses a possibility of increasing the wear and corrosion resistance of a low carbon steel surface after cathodic plasma electrolytic boronitrocarburising in a solution of boric acid, glycerin, and ammonium chloride, with the subsequent anodic plasma electrolytic polishing in an ammonium sulfate solution due to the formation of a modified structure consisting of a dense oxide layer and a diffusion layer below it, which contains up to 0.87% carbon, 0.80% nitrogen, and 0.87% boron upon reaching microhardness up to 970±20 HV. The competitive influence of the surface erosion under the action of discharges and high-temperature oxidation on the morphology and roughness of the surface is revealed.…”
Section: экспериментальные результаты и их обсуждениеunclassified
“…Результаты профилометрических исследований показали снижение шероховатости поверхности боронитроцементованной стали после АЭПП: после 2 мин полирования значение Ra снижается до исходной величины для необработанного образца при незначительной убыли его массы (таблица), что подтверждает избирательность удаления материала по выпуклой части профиля поверхности, а не всего профиля [16]. Стоит отметить, что полирование в сульфатном электролите способствует дополнительному окислению поверхности [20,21] The paper discusses a possibility of increasing the wear and corrosion resistance of a low carbon steel surface after cathodic plasma electrolytic boronitrocarburising in a solution of boric acid, glycerin, and ammonium chloride, with the subsequent anodic plasma electrolytic polishing in an ammonium sulfate solution due to the formation of a modified structure consisting of a dense oxide layer and a diffusion layer below it, which contains up to 0.87% carbon, 0.80% nitrogen, and 0.87% boron upon reaching microhardness up to 970±20 HV. The competitive influence of the surface erosion under the action of discharges and high-temperature oxidation on the morphology and roughness of the surface is revealed.…”
Section: экспериментальные результаты и их обсуждениеunclassified
“…In the past, researchers have focused on improving polishing e ciency and surface quality by optimizing process parameters. Wang et al [12] studied the effect of voltage on EPP, and found that when the power supply voltage is in the range of 270 ~ 330V, the surface roughness of the workpiece after polishing is the lowest, and when the power supply voltage is 270 ~ 290V, the energy consumption is the lowest. Wang et al [13] further studied the effects of polishing solution temperature, concentration and workpiece diving depth on surface roughness and material removal rate, and found that the order of the factors affecting the roughness and material removal rate are: Temperature > Concentration > Diving depth.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory, called the ‘streamer theory’, is based on streamer discharges [4,30,31]. A schematic drawing is provided in Figure 5.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In the literature, there are many theories about the mechanisms of polishing during the PeP process. Many papers mention melting the workpiece surface as the main, or as an important, part of the polishing mechanism [4,5,14,25,27,29,30,31,32].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation